ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH PROVINSI PAPUA TAHUN 2016-2020 - Hesty Theresia Salle; Arius Kambu; Elia Madatu Tandililing; Klara Wonar; Agustinus Salle (Universitas Cenderawasih, 2023)
This study aims to analyze the financial performance of the Papua provincial government in 2016-2020. The analysis method used is the descriptive analysis method. This study provides results that based on the independence ratio, the Regional Government of Papua Province is still in an instructive pattern, where the role of the Central Government is still dominant. Then from the calculation of the effectiveness and efficiency of PAD shows that the Regional Government has a good performance in realizing the planned PAD, as well as in terms of efficiency it is good enough to reduce regional spending. Then from the calculation of the income growth ratio, there is a trend of increasing the amount of regional income although it is not too high, as well as from the ratio of expenditure growth every year there is an increase in regional spending.